A review of impact testing on marine composite materials: Part IV – Scaling, strain rate and marine-type laminates. (15th September 2018) - Sutherland, L.S.
Abstract: Although composite materials are now used throughout the marine industry their susceptibility to impact events is still an unresolved problem. The complex nature of the problem in terms of the distinct material and impact event parameters specific to marine applications, damage tolerance and durability has been discussed in parts I, II and III of this review. Here, work addressing marine composite impact scaling and strain-rate effects, and impact studies not explicitly concerning marine applications yet considering laminates typical of the marine industry have been reviewed. Together with parts I, II and III, this paper gives a comprehensive review of 'marine impact on marine composites', providing a valuable resource for the marine industry and research fields.